The evolution of visual on Malaysian banknotes design / Mohamed Razeef Abdul Razak ... [et al] - Abdul Razak, Mohamed Razeef; Harun, Azahar; Md. Zain, Dzul Haimi; Hussin, Siti Nooraishah (Universiti Teknologi MARA, 2019)
The visual and design function on banknotes are not merely for decoration but instead in each design element and symbol created represents specific meaning. The banknote itself can be considered as a symbol and identity to a country due to its function as a national currency. It can also be perceived as a propaganda tool for a government. This paper aims to see to what extent the evolution of the visual design of Malaysian banknotes from the British colonial period up to the third series of the Malaysian banknotes issued by Bank Negara Malaysia. Thus, this study uses the approach of the history of art with visual analysis methods. In this study, each banknote is examined to identify the changes that occur and interpret why it is happening. The study found that the visual evolution of the design of the Malaysian banknotes has changed from time to time due to colonialism, war, independence, changes in government, changes in national policies, and the appointment of a new governor in addition to the upgrade of the banknotes security system. Looking at the design evolution of the Malaysian banknotes alone can make an impact in understanding the nation's history from the colonial period up to the time of the country's aspiration towards achieving a developed nation status. The visual elements and symbols used are not just an ornament on the banknotes but also evidence and valuable artifacts in understanding Malaysia and its history.